2010
DOI: 10.1002/dvdy.22495
|View full text |Cite
|
Sign up to set email alerts
|

Tinman is a direct activator of midline in the drosophila dorsal vessel

Abstract: Heart development requires a conserved core of transcription factors comprised of Nkx2.5, GATA and T-box family transcription factors. In Drosophila melanogaster, the Nkx2.5 gene tinman acts upstream of many cardiac genes including the Tbx20 homolog midline, a critical regulator of heart development in both flies and vertebrates. By testing genomic fragments containing clusters of consensus Tinman-binding sites, we identified a 4.3 kb fragment 5 0 of midline that directs reporter expression in all midline-expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Although bPAC is activated by blue light illumination, there is low-level residual cyclase activity in the dark (Schröder-Lang et al, 2007;Weissenberger et al, 2010;Ryu et al, 2011;Stierl et al, 2011). When expressed in the principal cells we observed a 1.7-fold increase in cellular cAMP levels attributable to bPAC when tissues were maintained in the dark, and PDE activity was inhibited by 3-isobutyl-1-methylxanthine (IBMX; data not shown).…”
Section: Cyclic Amp Exerts a Bimodal Control On Fluid Secretionmentioning
confidence: 67%
“…Although bPAC is activated by blue light illumination, there is low-level residual cyclase activity in the dark (Schröder-Lang et al, 2007;Weissenberger et al, 2010;Ryu et al, 2011;Stierl et al, 2011). When expressed in the principal cells we observed a 1.7-fold increase in cellular cAMP levels attributable to bPAC when tissues were maintained in the dark, and PDE activity was inhibited by 3-isobutyl-1-methylxanthine (IBMX; data not shown).…”
Section: Cyclic Amp Exerts a Bimodal Control On Fluid Secretionmentioning
confidence: 67%
“…GST pull-down assay GST pull-down assay was performed as described previously (Ryu et al, 2011). We purified GST, GST-Mid NT , and GST-Mid NT Á F41E following the manufacturer's protocol (GE Healthcare).…”
Section: Co-immunoprecipitationmentioning
confidence: 99%
“…Electrophoretic mobility shift assays (EMSA) were performed as previously described (Ryu et al, 2011). Double-stranded 32 P-endlabeled (10,000 cpm) oligonucleotides and purified GST-Mid NT (50 ng) were mixed in binding buffer containing 15 mM Hepes (pH 7.6), 100 mM KCl, 0.1 mM EDTA, 1 mM DTT, 12% glycerol, 0.25 mg/ml poly dI:dC, 0.25 mg/ml BSA, and incubated for 15 min on ice.…”
Section: Electrophoretic Mobility Shift Assay For Putative Mid Bindinmentioning
confidence: 99%
“…Interestingly, the role of Mid in selecting muscle fate choice between LT3 and LT4 is analogous to its function in the nervous system, where it mediates neuroblast fate specification (Buescher et al 2006;Gaziova and Bhat 2009). Mid and H15 also promote cell fate specification and morphogenesis in the Drosophila heart (Miskolczi-McCallum et al 2005;Qian et al 2005;, where mid is both a target and a regulator of the Tin transcription factor (Qian et al 2005;Ryu et al 2011;Jin et al 2013).…”
Section: Mid and The T-box Family Of Proteinsmentioning
confidence: 99%
“…Mid and its paralog H15 play partially redundant roles in specification and differentiation of the embryonic ectoderm (Buescher et al 2004) and in sensory organ precursor (SOP) cells in the eye imaginal disc (Das et al 2013). Mid and H15 also promote cardioblast specification and heart morphogenesis (Miskolczi-McCallum et al 2005;Qian et al 2005;, and it has been reported that Mid is both a target of the Tinman (Tin) transcriptional regulator (Qian et al 2005;Ryu et al 2011;Jin et al 2013) and is required for tin expression . Despite these well-characterized roles in the Drosophila embryo, no study of mid in the somatic mesoderm has been described.…”
mentioning
confidence: 99%